Gene Therapy: A Promising Approach for Neuroprotection in Parkinson’s Disease? - Valdés, Pamela; Schneider, Bernard L. (Frontiers in Neuroanatomy, 2016)
With the development of effective systems for gene delivery to the central nervous system (CNS), gene therapy has become a therapeutic option for the treatment of Parkinson’s disease (PD). Gene therapies that are the most advanced in the clinic have been designed to more effectively compensate for the lack of dopamine signaling in the basal ganglia and rescue the cardinal motor symptoms of PD. However, it remains essential to devise novel therapies to prevent neurodegeneration and disease progression. Since gene therapy has been initially proposed for the delivery of neurotrophins to support the survival and function of dopaminergic neurons, our understanding of PD etiology has changed dramatically. Genes implicated in familial forms of the disease and genetic risk factors associated with sporadic PD have been identified. The spreading of the α-synuclein pathology, as well as perturbations of the lysosomal and mitochondrial activities, appear to play critical roles in the pathogenesis. These findings provide novel targets for gene therapy against PD, but at the same time underline the complexity of this chronic disease. Here we review and discuss the successes and limitations of gene therapy approaches, which have been proposed to provide neuroprotection in PD.